Outdoor Learning Based on The Local Environment to Improve Student Learning Activities and Outcomes on Single Substance Material at MIN 2 Aceh Tamiang - Mazlan Mazlan; Nuraida Nuraida; Jelita Jelita; Ade Paramitha Utari; Desi Ardiani (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
Outdoor learning is very important in science learning, through outdoor learning it can foster students' curiosity about the environment. So the purpose of this study was to determine the activities and learning outcomes of science at MIN 2 Aceh Tamiang. This type of research is using classroom action research adopted from Kemmis and Tanggart which consists of 4 stages of planning, implementation, observation and the success of the first cycle can be seen from the results of reflection in the first cycle. The subjects of this research were carried out in class VB totaling 15 people. The instrument used to collect data using observation sheets and essay tests. The results showed that students' learning mastery in science learning cycle I was 68.66% and test results in cycle II were 88.66% and learning activities also increased by 75.46% in cycle I to 84.33% in cycle II. This shows an increase in students' learning mastery in science learning. Thus it can be concluded that the application of outdoor learning by utilizing the surrounding environment can increase student activity and learning outcomes on the material objects around us in class VB MIN 2 Aceh Tamiang.